Good Corporate Governance Implementation at PT. Chevron Pacific Indonesia (Bioremediation Corruption Case Study) (The Indonesian Journal of Business Administration, 2014)
Abstract— PT Chevron Pacific Indonesia (CPI) was conducting bioremediation or land recovery process in several areas which are in Sumatera Light North (SLN) and Sumatra Light South (SLS) to recover the land/soil condition which detected being contaminated by waste from oil production operation. The project related with bioremediation implementation was handled by two contractors which were PT Green Planet Indonesia and PT Sumigita Jaya that was chosen through tender mechanism. During the bioremediation implementation, Public Prosecutor accused that the project was not implemented according to the agreement, therefore, incurring allegation of corruption practice. CPI as the owner of the project allegedly has caused state to loss ± IDR 210 billion by proposing cost recovery expenses. This research tried to elaborate the potential issues which became the root cause problem of the weaknesses on CPI corporate governance practice in order to propose recommendation for improvement or addition in CPI internal system. Furthermore, this research will try to identify the weakness points in CPI internal system in the context of precaution and also bioremediation case management. After the root causes and miss-implementation of CPI internal corporate governance weaknesses are identified, therefore a new modification of corporate governance can be implemented in the system. Data collected in this research comes from primary and secondary data. The primary data collected from direct interaction with the source and observation. The secondary data collected from official court documents, CPI internal documents which being accessed for research purpose and literature studies related to the research. The analysis in this research was done using descriptive method by comparing data’s which were related with bioremediation case and the real facts. Keywords: Good Corporate Governance, Bioremediation, System, Precaution, Root Cause.